Effect of N, P and K humates on dry matter of Zea mays and soil pH, exchangeable ammonium and available nitrate - Ahmed, Osumanu Haruna; Shamsuddin, Rosliza; Nik Ab. Majid, Nik Muhamad; Jalloh, Mohamadu Boyie (Academic Journals, 2012)
Ammonia volatilization from surface-applied urea reduces urea-N use efficiency in crop production and it also pollutes the environment; it is an economic loss. A greenhouse study was conducted to confirm the effect of similar fertilizer formulations (N, P and K humates) on soil pH, exchangeable ammonium, available nitrate retention and dry matter of Zea mays cultivated on an acid soil (Typic Paleudults). The fertilizers were applied 10 days after planting (DAP) in each pot containing 10 kg of soil. Soil and plant samples (stems, leaves and roots) were collected at 31 DAP. Soil samples were analyzed for pH, ammonium, and nitrate content. Urea amended with humic acid (HA), acidified (HA+FA) and humin without TSP and MOP were not effective in increasing the dry matter production of the test crop. Urea amended with fulvic acid (FA) alone significantly increased plant dry matter. Complete fertilizer consisting urea, triple superphosphate (TSP) and mono triphosphate (MOP) amended with or without HA, FA, acidified HA and FA and humin significantly increased the dry matter of the test crop with significant retention of soil exchangeable ammonium. However, only the complete fertilizer with and without HA and humin amendment significantly retained soil available nitrate. The findings in this study may only be applicable to similar acid soils. The outcome of this study may contribute to the improvement of urea N use efficiency as well as reducing environmental pollution.